MENGENAL DOKTRIN DAN PRINSIP PIERCING THE CORPORATE VEIL DALAM HUKUM PERUSAHAAN - Dewi, Sandra (Kopertis Wilayah X, 2018)
Business entities in the business world are well-known that are already in the form of companies or those that are not yet companies. Based on its legal form, the company is divided into two, namely companies with legal status and those that are not legal entities. As an independent legal entity pursuant to Article 3 paragraph (1) the Limited Liability Company Law stipulates that the responsibility of PT shareholders is limited to the value of shares held in the company. Economically, the element of limited liability of the company's shareholders is an important factor as a motivating bait for the willingness of prospective investors to invest in the company. The formulation of the problem in this paper is: 1) how the piercing doctrine of the corporate veil in corporate law and 2) how to apply the principle of piercing the corporate veil in Indonesia. The type of writing used in this writing is a type of normative legal research. The doctrine of piercing the corporate veil in corporate law can be seen from: a) piercing the corporrate veil; b) the doctrine of fiduciary duty; c) self dealing transaction doctrine; d) doctrine corporate opportunity; e) doctrine businnes judgment rule; f) ultra vires and intra vires. Application of the Piercing Principles of the Corporate Veil in Indonesia: a) company shareholders; b) company founder; c) company directors; and d) commissioners of limited liability companies.